RELASI ANTARA AKSARA BIMA DAN AKSARA BUGIS-MAKASSAR - Muhammad Alfian Tuflih; Mayong Mayong (Universitas Negeri Makassar)
Abstract: The relationship between the Bima script and the Bugis-Makassarscript. This study aims to: 1) examine the relationship between the Bima andBugis-Makassar scripts; and 2) examine the closeness between the Bima Tribeand the Bugis-Makassar Tribe. This research is a qualitative research using aqualitative descriptive research design. The object of the research is the Bimascript with the Makassar Bugis script. These two characters will be compared tofind the relationship of form and ethnic closeness. The data analysis model used inthis study adopted an interactive data analysis model consisting of four activities,namely data collection, data reduction, data presentation, and conclusions. Theresults of this study indicate that the Bima script and the Bugis-Makassar scripthave a relationship because of the closeness of history and culture, and there is acloseness of script form